2015
DOI: 10.1016/j.molp.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Functional Analysis of Genes Expressed Ubiquitously in Rice

Abstract: Genes that are expressed ubiquitously throughout all developmental stages are thought to be necessary for basic biological or cellular functions. Therefore, determining their biological roles is a great challenge. We identified 4034 of these genes in rice after studying the results of Agilent 44K and Affymetrix meta-anatomical expression profiles. Among 105 genes that were characterized by loss-of-function analysis, 79 were classified as members of gene families, the majority of which were predominantly expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Promoter traps employing the GUS reporter gene system have been used to identify promoters involved in regulating tissue-specific and stress-responsive expression patterns (Jung et al, 2005, 2006, 2015). Our RNA-Seq data analysis revealed 98 genes showing >3 (log 2 scale)-fold upregulation by stress when compared with the control (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Promoter traps employing the GUS reporter gene system have been used to identify promoters involved in regulating tissue-specific and stress-responsive expression patterns (Jung et al, 2005, 2006, 2015). Our RNA-Seq data analysis revealed 98 genes showing >3 (log 2 scale)-fold upregulation by stress when compared with the control (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…These lines were obtained from a mixed pool of PFG T-DNA tagging lines from POSTECH in Korea (Lee et al, 2004; Jung et al, 2005, 2006, 2015; Hong et al, 2017; Wei et al, 2017). The resultant plantlets were then exposed to cold stress (4°C) for 0 or 24 h. Afterward, whole seedlings from all treatment groups were soaked for 8 h in a GUS -staining solution before their roots were photographed with a camera (Canon EOS 550D; Cannon, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…To confirm the expression patterns of candidate genes up-regulated by drought, we used two strategies: screening of promoter trap lines (as we have described previously) and generation of transgenic plants carrying the β-glucuronidase (GUS) reporter gene vector under the control of the target gene promoter (Fig. 2 ) 37 , 38 . For the former approach, we analyzed promoter trap lines for 70 candidate genes and found that only one had positive GUS expression that matched the activity of its co-segregating genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Screening of the promoter trap lines and GUS staining were performed as described previously 37 , 38 , 86 . We used a T-DNA-specific primer in the pGA2715 vector as well as gene-specific primer sequences to confirm, via PCR, the co-segregation of GUS expression and T-DNA insertion in rice Line PFG_3A-02918 (Table S8 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation